2021
DOI: 10.1097/inf.0000000000003155
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a Novel Culture System for Rapid Pathogen Identification and Detection of Cephalosporin Resistance in Neonatal Gram-negative Sepsis at a Tertiary Referral Unit in Harare, Zimbabwe

Abstract: Background: Neonatal sepsis accounts for a large proportion of neonatal deaths in sub-Saharan Africa. The lack of access to diagnostic testing and excessively long turnaround times to result contributes to delays in sepsis identification and initiation of appropriate treatment. This study aims to evaluate the novel InTrays COLOREX Screen and extended-spectrum beta-lactamase for rapid identification of bacterial pathogens causing sepsis and detection of resistance. Methods: Neonates with suspected sepsis admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…stroke (AIS) is not superior to intensive medical management (IMM) alone [28,29]. By IMM, we mean controlling patients' lipids, blood pressure, and blood glucose; regulating patients' lifestyles; enforcing smoking cessation; and encouraging exercise on the top of antiplatelet therapy [30]. However, even if IMM is strictly implemented in patients with sICAS, their 1-year stroke recurrence and mortality rates are maintained at more than 10% [31].…”
Section: Discussionmentioning
confidence: 99%
“…stroke (AIS) is not superior to intensive medical management (IMM) alone [28,29]. By IMM, we mean controlling patients' lipids, blood pressure, and blood glucose; regulating patients' lifestyles; enforcing smoking cessation; and encouraging exercise on the top of antiplatelet therapy [30]. However, even if IMM is strictly implemented in patients with sICAS, their 1-year stroke recurrence and mortality rates are maintained at more than 10% [31].…”
Section: Discussionmentioning
confidence: 99%
“…The InTray cassettes have already been successfully used in LMICs, targeting uropathogens from urine specimens [19] and ESBL Enterobacterales from blood cultures, where the combination of Colorex Screen and ESBL chromogenic media was able to reduce turnaround time significantly [20]. In this study, we tested the combination of InTray™ MH chocolate and Colorex Screen media for a wider application, in early orientation and diagnosis of sepsis, as a simple alternative to the classic combination of selective and non-selective media.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-prepared, commercially available culture media such as the InTray COLOREX Screen and ESBL agar plates (Biomed Diagnostics) have the potential to aid primary sample processing and transport to a referral laboratory, improve turnaround times for final result reporting to clinicians and aid early detection of ESBL-producing organisms. 13 The InTray media are small, sealable commercially produced agar plates, similar to media used commonly in many microbiology laboratories worldwide, but designed for inoculation in clinics or remote sites prior to transport to testing laboratories. Like other chromogenic media, different bacterial species produce different coloured colonies, allowing rapid presumptive identification.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Zimbabwe on the utility of the InTray COLOREX Screen and ESBL plates showed growth was seen on the plates within 5–10 h of incubation, which allowed for rapid identification and a reduction in time of 60% to reporting of results. 13 …”
Section: Introductionmentioning
confidence: 99%